Effects of mineral dust on global atmospheric nitrate concentrations - V. A. Karydis; A. P. Tsimpidi; A. Pozzer; M. Astitha; J. Lelieveld; J. Lelieveld (Atmospheric Chemistry and Physics, 2016)
This study assesses the chemical composition and global aerosol load of the major inorganic aerosol components, focusing on mineral dust and aerosol nitrate. The mineral dust aerosol components (i.e., Ca2+, Mg2+, K+, Na+) and their emissions are included in the ECHAM5/MESSy Atmospheric Chemistry model (EMAC). Gas/aerosol partitioning is simulated using the ISORROPIA-II thermodynamic equilibrium model that considers K+, Ca2+, Mg2+, NH4+, Na+, SO42−, NO3−, Cl−, and H2O aerosol components. Emissions of mineral dust are calculated online by taking into account the soil particle size distribution and chemical composition of different deserts worldwide. Presence of metallic ions can substantially affect the nitrate partitioning into the aerosol phase due to thermodynamic interactions. The model simulates highest fine aerosol nitrate concentration over urban and industrialized areas (1–3 µg m−3), while coarse aerosol nitrate is highest close to deserts (1–4 µg m−3). The influence of mineral dust on nitrate formation extends across southern Europe, western USA, and northeastern China. The tropospheric burden of aerosol nitrate increases by 44 % when considering interactions of nitrate with mineral dust. The calculated global average nitrate aerosol concentration near the surface increases by 36 %, while the coarse- and fine-mode concentrations of nitrate increase by 53 and 21 %, respectively. Other inorganic aerosol components are affected by reactive dust components as well (e.g., the tropospheric burden of chloride increases by 9 %, ammonium decreases by 41 %, and sulfate increases by 7 %). Sensitivity tests show that nitrate aerosol is most sensitive to the chemical composition of the emitted mineral dust, followed by the soil size distribution of dust particles, the magnitude of the mineral dust emissions, and the aerosol state assumption.